2016
DOI: 10.1177/0021998316637906
|View full text |Cite
|
Sign up to set email alerts
|

Fibre prestressed polymer-matrix composites: a review

Abstract: This article reviews the literature studies based on improving the mechanical properties of fibre-reinforced composites using fibre-prestressing method. The idea is characterized by pretensioning the fibres either elastically or viscoelastically prior matrix curing. The beginnings of the studies in this field were focused on reducing fibre waviness and breaking the weaker fibres by pretensioning the fibres to a relatively high stress level prior moulding process. In the last three decades, the concept of fibre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 104 publications
1
50
0
Order By: Relevance
“…The presence of compressive residual stress within the matrix increases the tensile capacity of the composites and reduces the initiation and propagation of cracks. 9,13 In addition, reducing fiber waviness in prestressed composites due to applying tensile stress to the fiber during curing of the matrix results in fibers within composites that can carry the transferred load to the matrix instantly and simultaneously which increases the tensile properties of composites. 13,27 The results also indicated that the prestressed composites which were prepared by using the estimated optimum FPL achieved the highest tensile strength and beyond the optimum FPL, the tensile properties start to decline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of compressive residual stress within the matrix increases the tensile capacity of the composites and reduces the initiation and propagation of cracks. 9,13 In addition, reducing fiber waviness in prestressed composites due to applying tensile stress to the fiber during curing of the matrix results in fibers within composites that can carry the transferred load to the matrix instantly and simultaneously which increases the tensile properties of composites. 13,27 The results also indicated that the prestressed composites which were prepared by using the estimated optimum FPL achieved the highest tensile strength and beyond the optimum FPL, the tensile properties start to decline.…”
Section: Resultsmentioning
confidence: 99%
“…Producing compressive residual stress within the cured matrix up to a certain value is beneficial and can enhance the mechanical properties of composites. 13 The optimum compressive residual stress can be determining by the following steps: (1) preparing prestressed composites with fixed fiber volume fraction by using different FPLs, (2) performing the required mechanical testing and determining the optimum FPL which is corresponding to the highest properties, and (3) substituting the optimum FPL in equation (9) …”
Section: Calculation Of the Optimum Compressive Residual Stress Withimentioning
confidence: 99%
“…In addition, the presence of microcracks increases the composites vulnerability to moisture absorption and chemical attacks, ultimately reducing their durability and mechanical performance (Guloglu et al,2016;Mostafa et al, 2017). Microcracks can form during cure when the induced residual stresses are greater than the resin yield strength.…”
Section: Microcracksmentioning
confidence: 99%
“…Building on this effort, a number of researchers adapted these advances in numerical simulation methods to the cure step of LCM processes, often following the impregnation (Khoun and Hubert, 2010;Michaud et al, 2002;Mostafa et al, 2017). In addition to optimizing cure, researchers aim to reduce residual stresses and limit the occurrence of cure induced defects (Baran et al, 2017;Dong et al, 2004;Khoun and Hubert, 2010;Mostafa et al, 2017;Nielsen et al, 2013;Ruiz and Trochu, 2006).…”
Section: Reduction Of Cure Induced Defects In Lcmmentioning
confidence: 99%
See 1 more Smart Citation